Roman Comedy - Manuwald, Gesine (Brill Research Perspectives in Humanities and Social Sciences Ser, 2020)
Intro -- Contents -- Roman Comedy -- Abstract -- Keywords -- 1 Introduction -- 2 Performance Contexts -- 2.1 Festivals -- 2.2 Theatre Buildings -- 2.3 Audiences -- 2.4 Actors and Staging -- 3 Editions, Commentaries, and Translations -- 4 Surveys and Reference Works -- 5 Fabula palliata -- 5.1 Themes I: Greek Intertexts, 'Translation', and Improvisation -- 5.2 Themes II: Topicality -- 5.3 Form I: Dramatic Structures and Techniques -- 5.4 Form II: Stock Characters -- 5.5 Form III: Language and Style -- 5.6 Form IV: Metre and Music -- 5.7 Authors I: Plautus -- 5.8 Authors II: Terence -- 5.9 Authors III: 'Minor Playwrights' -- 6 Fabula togata -- 7 Fabula Atellana -- 8 Mimus / Planipes -- 9 Pantomimus -- 10 Reception of Roman Comedy -- 11 Conclusions -- Bibliography -- Editions, Commentaries, Translations -- Secondary Literature.